Engineering Investigations of Dufour and Soret Effect on MHD Heat and Mass Transfer with Radiative Heat Flux in a Liquid over a Rotating Dick. - Ismail Mohmand, Muhammad; Bin Mamat, Mustafa; Shah, Qayyum (International Journal of Engineering and Technology, 2018)
This paper deals with the examination effect of Dufour and Soret Effect on MHD heat and mass transfer with radiative heat flux in a liquid over a rotating dick. The problem is solved by HAM (Homotopy Analysis Method). The arrangement of Non-Linear Partial Differential Equations (PDEs) which administer the stream, heat and mass exchange qualities is changed into Ordinary Differential Equations (ODEs). It is discovered from the current exploration that Dufour and radiation impacts cause diminishments in the liquid temperature. The effect of suction diminishes the speed, temperature, whatâ€™s more, focus profiles essentially in the limit layer.Â Â